2001
DOI: 10.1002/1438-5171(200107)2:2<105::aid-simo105>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Atomic Force Microscope Imaging of Supported Lipid Bilayers

Abstract: In situ AFM images of phospholipase A 2 (PLA 2 ) hydrolysis of mica-supported one-and two-component lipid bilayers are presented. For one-component DPPC bilayers an enhanced enzymatic activity is observed towards preexisting defects in the bilayer. Phase separation is observed in two-component DMPC-DSPC bilayers and a remarkable enhanced hydrolytic activity of the PLA 2 -enzyme for the DMPC-rich phase is seen. Furthermore, in a supported double bilayer system a characteristic ripple structure, most likely rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…We also note that past studies have demonstrated that PLA 2 partially extracts lipids from an interface prior to cleavage. [54][55][56][57][58][59] It is possible that the…”
mentioning
confidence: 99%
“…We also note that past studies have demonstrated that PLA 2 partially extracts lipids from an interface prior to cleavage. [54][55][56][57][58][59] It is possible that the…”
mentioning
confidence: 99%
“…This general picture of sPLA 2 activation is supported by detailed analyses of atomic force microscopy images of solid-supported bilayers in the presence of sPLA 2 in the various stages before and after the lag phase [30,33,34]. These analyses strongly suggest that sPLA 2 attacks at areas with structural defects, such as domain boundaries, at regions with accumulated hydrolysis products, and at the edges of pre-existing holes in the bilayer.…”
Section: Temperature (8c)mentioning
confidence: 75%
“…Determination of the lateral organization of liposomal membranes on scales ranging from 10 to 1000 nm has proved elusive [27][28][29][30]. However, indirect and direct evidence from recent studies of model membranes as well as biological membranes has suggested that membranes are laterally heterogeneous and structured in terms of domains and so-called rafts [31].…”
Section: Lateral Microstructure Of Lipid Bilayers and Its Influence Omentioning
confidence: 99%
See 2 more Smart Citations